46.4k views
5 votes
If x^2 +x-12 is a factor of x^3+ax^2-10x-b then find the values of a and b

User Twalberg
by
4.8k points

1 Answer

4 votes

Answer:

a=3

b=24

Explanation:

If
x^2+x-12 is a factor of
x^3+ax^2-10x-b, then the factors of
x^2+x-12 must also be factors of
x^3+ax^2-10x-b.

So what are the factors of
x^2+x-12? Well the cool thing here is the coefficient of
x^2[tex] is 1 so all we have to look for are two numbers that multiply to be -12 and add to be positive 1 which in this case is 4 and -3.</p><p>-12=4(-3) while 1=4+(-3).</p><p></p><p>So the factored form of [tex]x^2+x-12 is
(x+4)(x-3).

The zeros of
x^2+x-12 are therefore x=-4 and x=3. We know those are zeros of
x^2+x-12 by the factor theorem.

So x=-4 and x=3 are also zeros of
x^3+ax^2-10x-b because we were told that
x^2+x-12 was a factor of it.

This means that when we plug in -4, the result will be 0. It also means when we plug in 3, the result will be 0.

Let's do that.


(-4)^3+a(-4)^2-10(-4)-b=0 Equation 1.


(3)^3+a(3)^2-10(3)-b=0 Equation 2.

Let's simplify Equation 1 a little bit:


(-4)^3+a(-4)^2-10(-4)-b=0


-64+16a+40-b=0


-24+16a-b=0


16a-b=24

Let's simplify Equation 2 a little bit:


(3)^3+a(3)^2-10(3)-b=0


27+9a-30-b=0


-3+9a-b=0


9a-b=3

So we have a system of equations to solve:

16a-b=24

9a-b=3

---------- This is setup for elimination because the b's are the same. Let's subtract the equations.

16a-b=24

9a-b= 3

------------------Subtracting now!

7a =21

Divide both sides by 7:

a =3

Now use one the equations with a=3 to find b.

How about 9a-b=3 with a=3.

So plug in 3 for a.

9a-b=3

9(3)-b=3

27-b=3

Subtract 27 on both sides:

-b=-24

Multiply both sides by -1:

b=24

So a=3 and b=24

User Daniel Lobo
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.